Enhancement of Madrasah Ibtidaiyah's Student Management - Seri Kamelia; Dahlia; Khalid Fitri; Ahmadi; Marsiah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2023)
Student management is necessary for the educational process to be successful. Located on Jalan Ramin Palangka Raya, Madrasah Ibtidaiyah Negeri II Palangka Raya is a popular Islamic secondary school that many families send their kids to. The purpose of the study was to identify and characterize the following aspects: Planning for student management, 2) welcoming new students, 3) student orientation events, 4) student records and reports, 5) student growth and supervision, and a description of how student management is being implemented at Madrasah Ibtidaiyah Negeri II Palangka Raya are all included. This study employed a qualitative approach to explain the phenomenon of student management implementation at Madrasah Ibtidaiyah Negeri II Palangka Raya. Observation, interviews, documentation studies, and triangulation were the methods used to acquire data; analysis, validity testing, and conclusion drafting came next. Regarding the research's issues, secondary informants provided support for the Headmaster, who served as the primary informant. The study's findings indicate that: 1) Madrasah Ibtidaiyah Negeri II Palangka Raya's student planning began with an examination of the needs of the students, then moved on to student recruitment and selection. 2) A Committee of Penerimaan Peserta Didik Baru (PPDB) oversaw the recruitment and selection of students. A few teachers were chosen by the headmaster to lead the committee. The committee chose new pupils using two criteria: the candidate's record of accomplishment and regular method. 3) The Vice Headmaster of Student Affairs oversaw and controlled the OSIM's student orientation programs. 4) Student records and reports have been created, for example, by keeping track of students' daily attendance lists to learn about their academic progress and provide study support. 5) Student development and supervision were carried out through intra- and extracurricular activities like student athletics, student scouting, and OSIM. To foster the student's interest and talent, all of the activities were carried out under constant observation.